2022
DOI: 10.1111/1440-1630.12811
|View full text |Cite
|
Sign up to set email alerts
|

Co‐development of the ENVISAGE‐Families programme for parents of children with disabilities: Reflections on a parent–researcher partnership

Abstract: Introduction:In childhood disability research, the involvement of families is essential for optimal outcomes for all participants. ENVISAGE (ENabling VISions And Growing Expectations)-Families is a programme comprising five online workshops for parents of children with neurodevelopmental disorders.The workshops aim to introduce parents to strengths-based perspectives on health and development. The research is based on an integrated Knowledge Translation (iKT) approach, in which knowledge users are involved thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Our conclusions reflect many of the themes identified in other co-produced and co-delivered studies with family carers (Borek et al , 2018; Pozniak et al , 2022).…”
Section: Experiences Reflections and Implicationssupporting
confidence: 80%
“…Our conclusions reflect many of the themes identified in other co-produced and co-delivered studies with family carers (Borek et al , 2018; Pozniak et al , 2022).…”
Section: Experiences Reflections and Implicationssupporting
confidence: 80%
“…The proposed sample size is similar to approaches used in other mixed-methods research for programme codevelopment in children with neurodevelopmental disabilities (including cerebral palsy). 32 33 It is acknowledged that some parent/caregiver participants may have a relationship with child participants, and this may introduce bias in the sampling. Nonetheless, these participants will remain eligible to take part in the study as the lived experience of SDH concerns is individualistic and may differ between children and their parent/caregiver.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, approximately 10 children with cerebral palsy, 10 parents/caregivers, and 15 clinicians will participate in components 2 and 3. The proposed sample size is similar to approaches used in other mixed-methods research for programme codevelopment in children with neurodevelopmental disabilities (including cerebral palsy) 32 33. It is acknowledged that some parent/caregiver participants may have a relationship with child participants, and this may introduce bias in the sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Four papers focus on occupational therapy education, with three discussing the involvement of lived experience experts in mental health (Happel et al, 2022; Logan et al, 2022; Scanlan et al, 2022) and one discussing consumers providing feedback to students during practice placements (Bevitt et al, 2022). Two focus on the involvement of consumers in developing services (Harris et al, 2022; Pozniak et al, 2022), and three focus on consumer partnerships in research (Chapman et al, 2022; Cox et al, 2022; Liddle et al, 2022).…”
mentioning
confidence: 99%
“…Moving to occupational therapy service development, the two included articles provide examples of occupational therapy programmes that have been developed in collaboration with consumers. Pozniak et al (2022) describes the process of co‐developing a programme for parents of children with disabilities. The authors, including consumer‐investigators, identified seven key ingredients for successful parent–researcher working relationships, which included consistent communication, clear roles and expectations, onboarding and feedback, flexibility, understanding, self‐reflection, and funding.…”
mentioning
confidence: 99%